OʻQUV-METODIK TA’MINOTLARGA ILG‘OR XALQARO PLATFORMALARNI INTEGRATSIYA QILISh USULLARI - Kenesbayev, A. (SCIENCE and SOCIETY, 2025)
This article analyzes the methods of integrating advanced international platforms into educational and methodological support. The study examines the possibilities of improving the quality of education by integrating international platforms into national digital platforms.